Precarious Habitus: Insights from working and living precariously in Auckland, New Zealand - Galic, Marko (New Zealand Sociology, 2025)
The following article introduces a new concept of precarious habitus. Based on workers-centred responses from the qualitative research on work and precarity, situated in Auckland, New Zealand, the paper focuses on a relationship between precarious work and precarious life that creates the state of precarity – a mode of domination and structural marginalisation on the one hand, and a broader existential condition of uncertainty and social vulnerability on the other. The article reveals both structural constraints that precarious workers, particularly the Māori precariat and migrant workers, face on a daily basis, and the making of certain social dispositions that workers internalise in order to get by. The paper emphasises three dimensions of precarity that create precarious habitus: structural constraints of precarious work; the making of precarious habitus in relation to migrant worker exploitation and marginalisation; and the price of escaping precarity by adopting certain social dispositions.